The importance of celiac on treatment of calf diarrhea - Veysi Aslan; İsmail Şen (Eurasian Journal of Veterinary Sciences)
In this investigation, it was studied on 20 neonatal calves suffered from diarrhea. After elinical examination, blood sample was taken from jugular vein and WBC, PCV and blood pH were measured. The commerical drug Celiac which contains various e!ektrolites and vitamin and natural fibers was given orally to each calve suffered from diarrhea. Daily blood and elinical examinations were checked up until the end of study. At the end of study 17 calves out of 20 were observed to turn their health and diarrhea was disappeared. Three calves were died/euthenased during the study.